The Resistance Mechanisms and Treatment Strategies for ALK-Rearranged Non-Small Cell Lung Cancer - Pan, Yue; Deng, Chao; Qiu, Zhenhua; Cao, Chenghui; Wu, Fang (Frontiers in Oncology, 2021)
Anaplastic lymphoma kinase (ALK) is a validated molecular target non-small-cell lung cancer (NSCLC). The use of targeted therapy with tyrosine kinase inhibitors (TKIs) has led to unprecedented survival benefits. However, the clinical benefit of targeting ALK using TKIs is almost universally limited by the emergence of drug resistance. The landscape of resistance mechanisms and treatment decisions has become increasingly complex. Therefore, continued research into new drugs and combination therapies is required to improve outcomes in NSCLC. In this review, we explore the mechanism of drug resistance of ALK-TKI in advanced NSCLC, hoping to provide certain theoretical basis and research ideas for solving the problem of drug resistance.